Persepsi Mahasiswa Akuntansi Terhadap Independensi Akuntan Publik: Studi Empirik pada Mahasiswa Akuntansi di Bandung - Trimanto Setyo Wardoyo; Tatik Budiningsih; Herman Kambono; Elvira Veronica (Universitas Kristen Maranatha, 2021)
Abstract This study aims to determine the perceptions of accounting students towards the independence of public accountants in the city of Bandung. Positive perceptions indicate that the accounting profession, especially public accountants, has a proper place in accounting students. Through a questionnaire distributed with a sample of accounting students in the city of Bandung, with a target sample size of 60 students. From 137 respondents gathered, it can be seen based on the results of the analysis that students majoring in accounting in Bandung perceive that public accountants in Indonesia are not independent. In addition, the results of this study are expected to be inference for accounting students in Indonesia. The results of this study also show that there are differences in the perceptions of students majoring in accounting in Bandung who have never and who have taken auditing courses on the independence of public accountants in Indonesia. Keywords: Perception, Independence, Accounting Profession, and Public Accountant